A237 IMPROVEMENT IN ABDOMINAL SYMPTOMS WITH LINACLOTIDE IN PATIENTS WITH IRRITABLE BOWEL SYNDROME WITH CONSTIPATION: RESULTS FROM A PHASE 3B TRIAL. (4th March 2021) - Sidani, S; Boutros, K; Sayuk, G S; Gonzalez, H; Brenner, D M
Abstract: Background: Linaclotide (LIN) is a guanylate cyclase-C agonist approved to treat irritable bowel syndrome with constipation (IBS-C) in adults. Abdominal symptoms are important to patients with IBS-C. In a recent Phase 3b study, LIN significantly improved a composite score of abdominal bloating, pain, and discomfort (Abdominal Score), which was used as the primary endpoint in the study. Aims: To evaluate the efficacy of LIN for improving additional efficacy abdominal symptom endpoints in a randomized, double-blind, placebo (PBO)-controlled Phase 3 study of LIN in patients with IBS-C. Methods: Adults with IBS-C were randomized to PBO (N=308) or LIN 290 μg (N=306) once daily for 12 weeks. Patients recorded their daily abdominal symptoms, including the individual items of bloating, pain, and discomfort, using an 11-point scale (0–10; 0=none, 10=worst possible). The primary endpoint was the Abdominal Score. Additional efficacy endpoints included 6/12-week abdominal pain and constipation (APC)+1 responder, 6/12-week abdominal bloating responder, 6/12-week abdominal pain responder, and 6/12-week abdominal discomfort responder. For individual symptoms, a responder was a patient who had an improvement from baseline of ≥2 points in the respective endpoint for ≥6 of the 12 weeks. Changes from baseline (CFB) over 12 weeks in abdominal bloating, pain, and discomfort were evaluated using a mixed model with repeated measures framework. Proportions of responders were compared between groups for each responder endpoint using a Cochran-Mantel-Haenszel test. Results: 614 patients (mean age, 46.7 years; 81% female; similar baseline abdominal symptoms) were randomized. LIN-treated patients had greater least-squares mean (LSM) CFB in abdominal bloating (LSM difference [95% CI]: –0.889 [–1.249, –0.530], p<0.001), pain (–0.881 [–1.238, –0.524], p<0.001), and discomfort (–0.837 [–1.196, –0.478], p<0.001) compared to PBO-treated patients. There was a greater proportion of LIN-treated vs. PBO-treated patients who were 6/12-week APC+1 (29% vs. 17%; p=0.0003), bloating (40% vs. 24%; p<0.001), pain (42% vs. 25%; p<0.001), and discomfort (42% vs. 26%; p<0.001) responders (Figure ). Diarrhea was the most common treatment-emergent adverse event (LIN: 4.6%; PBO: 1.6%). Conclusions: LIN significantly improved multiple abdominal symptom and secondary responder endpoints in patients with IBS-C. These results support the effectiveness of LIN for improving a spectrum of abdominal symptoms in IBS-C. Funding Agencies: This study was sponsored by Allergan plc, Dublin, Ireland (prior to acquisition by AbbVie Inc.). Writing and editorial assistance were provided to the authors by Brittany Y. Jarrett, PhD, Jane Beck, MA, and Rebecca Fletcher, BA(Hons) of Complete HealthVizion, Inc., Chicago, IL, USA and funded by Allergan plc (prior to acquisition by AbbVie Inc.).